Compartmentalized polymerization in aqueous and organic media to low-entangled ultra high molecular weight polyethylene. Issue 21 (7th May 2021) - Wimmer, Florian P.; Ebel, Viktoria; Schmidt, Felix; Mecking, Stefan
Abstract : Catalytic polymerization in compartmentalized aqueous or non-aqueous media, respectively, with functional-group tolerant Ni(ii ) catalysts yields low-entangled UHMWPE. Abstract : Catalytic copolymerization with functional group tolerant lipophilic Ni(ii ) catalysts in aqueous emulsion-type polymerization or dispersion polymerization in organic solvents (THF, n -heptane) yields ultra high molecular weight polyethylene (UHMWPE) as submicron- or micron-sized, respectively, particles. Precise multiblock copolymers with crystallizable C46 polyethylene blocks and amorphous soluble polybutene blocks, as well as a random ethylene-octene copolymer with similar block lengths were suitable for particle stabilization in the organic dispersion polymerizations.